Supramolecular Fe3O4@PEG/−diaza crown ether@Ni: a novel magnetically reusable nano catalyst for the clean synthesis of 2‐aryl‐2, 3‐dihydroquinazolin‐4(1H)‐ones. (22nd April 2019) - Aalinejad, Michael; Noroozi Pesyan, Nader; Heidari, Nosrat; Batmani, Hana; Danandeh Asl, Aria
Abstract : Ni@diaza crown ether complex supported on magnetic nanoparticle was provided by grafting technique. The catalytic activity of Fe3 O4 @diaza crown ether@Ni was explored through one‐pot synthesis of 2, 3‐dihydroquinazolin‐4(1 H )‐ones and it was used as an efficient and recoverably constant nanocatalyst. FT‐IR, SEM, TEM, XRD, BET, ICP, EDS, and TGA techniques were employed to specify the nanocatalyst. This heterogeneous catalyst demonstrated acceptable recyclability and could be used again several times with no considerable loss of its catalytic activity. Abstract : Supramolecular Ni@diaza crown ether complex supported on magnetic nanoparticle was provided. This nanocatalyst was used for the clean synthesis of 2‐aryl‐2, 3‐dihydroquinazolin‐4(1H)‐ones and used again at least six times with no considerable loss of its catalytic activity.